2004
DOI: 10.1038/sj.onc.1207583
|View full text |Cite
|
Sign up to set email alerts
|

Binding of RNA to p53 regulates its oligomerization and DNA-binding activity

Abstract: The C-terminus of p53 is responsible for maintaining the latent, non-DNA-binding form of p53. However, the mechanism by which the C-terminus regulates DNA binding is not yet fully understood. We show here that p53 interacts with RNA via its C-terminal domain and that disruption of this interaction, by RNase A treatment, truncation or phosphorylation of the C-terminus, restores DNA-binding activity. Furthermore, the oligomerization of p53 is significantly enhanced by disrupting the interaction between p53 and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 43 publications
0
43
1
Order By: Relevance
“…As p53 interacts with RNA via its C-terminal regulatory domain, 13 we used this domain in the docking analysis. The p53 (C-terminal regulatory domain) used in the docking procedure was derived from Protein Data Bank entry 1DT7.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As p53 interacts with RNA via its C-terminal regulatory domain, 13 we used this domain in the docking analysis. The p53 (C-terminal regulatory domain) used in the docking procedure was derived from Protein Data Bank entry 1DT7.…”
Section: Resultsmentioning
confidence: 99%
“…The RING-finger domain in the carboxyl terminal of the MDM2 is known to bind RNA specifically in a sequence-specific manner, 12 whereas p53 interacts with RNA via its C-terminal regulatory domain. 13 Our study comprised of computer-aided RNA structure modeling of circ-Foxo3 employing minimum free energy algorithm and machine translation system followed by its molecular interaction with MDM2 (RING-finger domain) and p53 (C-terminal regulatory domain) that includes docking, scoring, clustering, and refinement of the most promising models. The interaction was further confirmed by an approach of molecular experiments to explicate the biological functions of circ-Foxo3.…”
mentioning
confidence: 99%
“…73 In addition, evidence suggests that the interaction of p53 with a consensus DNA sequence stabilizes this protein and inhibits its aggregation 74 ; however, it is also possible that longer DNA chains could lead to polymerization. 75 Although the interaction between p53 and RNA has been reported, [76][77][78] aggregates produced by this interaction have not yet been identified. Poly-adenylated RNA has been found in aggresomes that contain several key proteins (including p53) involved in cancer and neurodegenerative diseases.…”
Section: Molecular Partners Involved In P53 Aggregationmentioning
confidence: 99%
“…Similarly, Galy et al reported that recombinant p53 can bind the 5'-UTR of the FGF-2 mRNA [18]. In contrast, reports of p53 RNA-RNA annealing activity [13] and sequence-nonspecific RNA binding [4,6,7,19] suggested that p53 binds RNA promiscuously. Acetylation of four p53 C-terminal lysine residues eliminates detectable RNA binding in vitro [7], as it does for sequence-nonspecific DNA binding [8].…”
Section: Introductionmentioning
confidence: 95%
“…A prior study of p53-RNA interactions in human cells suggested that RNA is coimmunoprecipitated with p53 using Do-1 and Do-7 antibodies, which recognize N-terminal p53 epitopes (Fig. 1A,B; [19]). Recovered RNAs were detected by radiolabeling but were not cloned [19].…”
Section: Introductionmentioning
confidence: 99%